2015
DOI: 10.1186/s13012-016-0488-1
|View full text |Cite
|
Sign up to set email alerts
|

An integrated general practice and pharmacy-based intervention to promote the use of appropriate preventive medications among individuals at high cardiovascular disease risk: protocol for a cluster randomized controlled trial

Abstract: BackgroundCardiovascular diseases (CVD) are responsible for significant morbidity, premature mortality, and economic burden. Despite established evidence that supports the use of preventive medications among patients at high CVD risk, treatment gaps remain. Building on prior evidence and a theoretical framework, a complex intervention has been designed to address these gaps among high-risk, under-treated patients in the Australian primary care setting. This intervention comprises a general practice quality imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…With the remuneration of community pharmacies' non-dispensing services a contested and divisive area of health policy, 28 one solution might be to invest in technology to better connect GP services with the services provided by community pharmacists rather than create and fund 'new' adherence services. 29,30 This is particularly relevant with respect to pharmacists' dispensing of generic medications, whose different colours, shapes and sizes could confuse patients. Alternatively, the inclusion of pharmacists in the 'Health Care Home', as done in other contexts, could be explored.…”
Section: Discussionmentioning
confidence: 99%
“…With the remuneration of community pharmacies' non-dispensing services a contested and divisive area of health policy, 28 one solution might be to invest in technology to better connect GP services with the services provided by community pharmacists rather than create and fund 'new' adherence services. 29,30 This is particularly relevant with respect to pharmacists' dispensing of generic medications, whose different colours, shapes and sizes could confuse patients. Alternatively, the inclusion of pharmacists in the 'Health Care Home', as done in other contexts, could be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the physicians had no electronic access to the test results and reports of radiology and pharmaceutical prescriptions of their patients in necessary situations and for this reason, they are not able to constantly check the clinical status of their patients. In this regard, the study of Hayek et al showed that the physicians recorded patients’ pharmaceutical prescriptions in the computerized system of their clinics, and these requests had an integrated relation with the electronic medical record of their patients, and the requests were forwarded to the pharmacies after checking the pharmaceutical interferences and then the patients received their pharmaceutical prescriptions after the reference to the pharmacies ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…11,13,31 Results of various under way trials (SECURE, PolyIran, TIPS-3, and HOPE-4, among others) are expected to provide the evidence about the effects and safety of polypills. [32][33][34] It is also worth highlighting that many trials that have evaluated prevention is yet to be demonstrated. 11,13,21 The concept of polypills in the primary prevention of CVD was first introduced by Wald and Law, 14 who presented these drugs as a mass treatment strategy to reduce CVD by more than 80%.…”
Section: Available 11mentioning
confidence: 99%
“…It is true, however, that most of these effects were not significantly different from those induced by usual medications . Results from ongoing trials (SECURE [Secondary Prevention of Cardiovascular Disease in the Elderly Trial; NCT02596126] and INTEGRATE [Integrated Combination Therapy, Electronic General Practice Support Tool, Pharmacy Led Intervention and Combination Therapy Evaluation; ACTRN12616000233426] and the SCCS Polypill Pilot [NCT02278471] and PolyIran [NCT01271985] trials and the related PolyIran Liver [NCT01245608], TIPS‐3 [The International Polycap Study 3; NCT01646437], and HOPE‐4 [Heart Outcomes Prevention and Evaluation 4; NCT01826019] trials) are urgently awaited to clarify these issues. Nonetheless, polypills seem to surpass usual cardiovascular treatments when considering the ease of prescription and significant increase in adherence.…”
Section: Expected Benefits Of Polypills In Lmicsmentioning
confidence: 99%
See 1 more Smart Citation